2022
DOI: 10.1111/and.14360
|View full text |Cite
|
Sign up to set email alerts
|

Association between the international index of erectile function‐15 and female sexual function index in Chinese infertile couples

Abstract: Infertility has a detrimental impact on the sexual function of involuntarily childless couples. However, the effect of male sexual function on female partner's sexual function in infertile couples remains unknown. In order to explore the association between these couples' sexual function, 324 consecutive couples with infertility and 326 female‐age‐matched fertile couples were enrolled in this study. The female sexual function index (FSFI) and sexual history were evaluated in female partners. In addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…21 According to previous studies, female sexual function parameters were significantly associated with their male partners' erectile function and sexual desire. 8,15,21 A previous study has found that 55% of female partners of men with ED reported 1 or more female sexual dysfunctions.…”
Section: Jama Network Open | Urologymentioning
confidence: 99%
See 4 more Smart Citations
“…21 According to previous studies, female sexual function parameters were significantly associated with their male partners' erectile function and sexual desire. 8,15,21 A previous study has found that 55% of female partners of men with ED reported 1 or more female sexual dysfunctions.…”
Section: Jama Network Open | Urologymentioning
confidence: 99%
“…Approximately 43% of women in the US experience female sexual dysfunction, 7 while in China, female sexual dysfunction is even more prevalent, possibly associated with China's relatively conservative sexual culture. 8,9 An internet-based study conducted by Du et al 10 found the prevalence of female sexual dysfunction in China was 60.2%. However, despite the high prevalence of sexual dysfunction, it continues to remain underdiagnosed and undertreated, especially female sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations